Absorption, distribution, metabolism, and excretion of cenerimod, a selective S1P1 receptor modulator in healthy subjects. (2nd August 2020) - Boof, Marie-Laure; van Lier, Jan Jaap; English, Stephen; Fischer, Hartmut; Ufer, Mike; Dingemanse, Jasper
Abstract: Cenerimod is a sphingosine-1-phosphate 1 receptor modulator under development for treatment of systemic lupus erythematosus. This single-centre, open-label, single-dose study investigated the mass balance and excretion routes and aimed at identifying and quantifying cenerimod metabolites in plasma, urine, and faeces after oral administration of 2 mg/100 μCi (3.7 MBq) of 14 C-cenerimod. Total mean cumulative recovery was 84% of the administered dose (58–100% in faeces and 4.6–12% in urine). In a 0–504 h cross-subject area under the curve plasma pool, cenerimod and two metabolites were detected accounting for 78, 6.0, and 4.9% of total radioactivity, respectively, i.e. no major metabolite was identified in plasma. Cenerimod was only detected in faeces and accounted for 17% of the radioactivity excreted in this matrix. The metabolite M32 was detected in both urine and faeces and represented 23% and 66% of radioactivity excreted in these matrices, respectively. Other metabolites of unknown structure were detected in small amounts. Overall, M32 and cenerimod accounted for 52% and 13%, respectively, of the total radioactivity recovered. Among the excreted metabolites, only the non-enzymatically formed M32 represented more than 25% of total drug-related material. Therefore, no pharmacokinetic drug–drug interaction studies are foreseen.